Efficacy and tolerability of perampanel in patients with seizures in real-world clinical practice: A systematic review and meta-analysis - Liyan Hou; Jingjing Yang; Xuan Zhang; Na Li; Sheng Li; Lei Zhang; Jie Zhao; Qingshan Wang; Qingshan Wang (Frontiers Media S.A., 2023)
Objectives: The aim of this study was to systematically review the efficacy and tolerability of perampanel (PER) when used as add-on treatment or monotherapy in patients with epilepsy aged 12 years and older in routine clinical practice.Methods: Electronic and clinical trials databases were searched for observational studies of PER published up to 1 March 2022. The outcomes of interest were responder rates, adverse effects (AEs), and withdrawal rates. Subgroup analyses were performed to explore the potential factors that might affect the efficacy and safety of PER usage.Results: A total of 56 studies, which included 10,688 patients, were enrolled. The results showed that after 3, 6, and 12 months of PER treatment, the pooled 50% responder rates in patients with epilepsy were 50.0% (95% CI: 0.41-0.60), 44.0% (95% CI: 0.38-0.50), and 39.0% (95% CI: 0.31-0.48), respectively, and the pooled seizure-free rates were 24.0% (95% CI: 0.17-0.32), 21.0% (95% CI: 0.17-0.25), and 20.0% (95% CI: 0.16-0.24), respectively. Subgroup analyses revealed that the efficacy of PER could be affected by the way in which PER is administrated. Patients in the groups where PER was used as the first add-on, primary monotherapy, or combined with non-enzyme-inducing AEDs (non-EIAEDs) displayed a high 50% responder rate and seizure-free rate when compared with those in the late add-on, conversion therapy, or combined with the EIAEDs groups, respectively. Furthermore, the incidences of AEs at 3, 6, and 12 months of PER treatment were 46% (95% CI: 0.38-0.55), 52.0% (95% CI: 0.43-0.60), and 46.0% (95% CI: 0.40-0.52), respectively. The withdrawal rates due to AEs were 8.0% (95% CI: 0.06-0.11), 16.0% (95% CI: 0.13-0.20), and 16% (95% CI: 0.11-0.21) at 3, 6, and 12 months of PER treatment, respectively. Subgroup analyses showed a higher withdrawal rate in the rapid (30%, 95% CI: 0.22-0.38) than in the slow (12%, 95% CI: 0.06-0.18) titration group.Conclusion: Altogether, PER was effective and could be fairly tolerated in both short-term and long-term usage in patients with epilepsy in routine clinical practice. Furthermore, PER appeared to be more effective when PER was used as the first add-on, monotherapy, or concomitant with non-EIAEDs.Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022384532.